Efektivitas Teknik Kebebasan Emosional Spiritual Pada Peningkatan Kualitas Hidup Pada Pasien Pasca Stroke - Abdul Herman Syah Thalib; Fitri J Saleh (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: The prevalence of stroke each year is increasing. Strokes that are not treated properly will cause a decrease in the patient’s quality of life. Aim: provide an overview of evidence from previous studies on quality of life in post-stroke patients before and after spiritual emotional freedom technique intervention. Method: Conduct a literature review by searching through electronic databases namely Garuda, Pubmed, and Google Scholar, and obtained 3 relevant research articles from 2011-2021 based on inclusion and exclusion criteria. Results: After being given the ACT of SEFT found an improvement in quality of life in post-stroke patients. Conclusion: Terapi SEFT (Spiritual Emotional Freedom Technique) is effective in improving the quality of life in post-stroke patients.